2011
DOI: 10.7150/ijbs.7.1334
|View full text |Cite
|
Sign up to set email alerts
|

Paratransgenic Control of Vector Borne Diseases

Abstract: Conventional methodologies to control vector borne diseases with chemical pesticides are often associated with environmental toxicity, adverse effects on human health and the emergence of insect resistance. In the paratransgenic strategy, symbiotic or commensal microbes of host insects are transformed to express gene products that interfere with pathogen transmission. These genetically altered microbes are re-introduced back to the insect where expression of the engineered molecules decreases the host's abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(68 citation statements)
references
References 49 publications
0
67
0
1
Order By: Relevance
“…14,23,51 We cannot discard the route of direct transmission between triatomines by coprophagy or cannibalism, 25,[52][53][54] given that all triatomines must obtain their symbionts at least once in their lifetime, probably by coprophagy. 25,55 Most of the time, field insects are starving, which enhances their cannibalistic behavior towards other triatomines that were able to feed, probably acquiring T. cruzi in the process, in case that the engorged insect was infected. 53 We report high infection rates with T. cruzi in adults found in sylvatic and domiciliary habitats, and lower levels of infection among the nymphal instars found in the sylvatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…14,23,51 We cannot discard the route of direct transmission between triatomines by coprophagy or cannibalism, 25,[52][53][54] given that all triatomines must obtain their symbionts at least once in their lifetime, probably by coprophagy. 25,55 Most of the time, field insects are starving, which enhances their cannibalistic behavior towards other triatomines that were able to feed, probably acquiring T. cruzi in the process, in case that the engorged insect was infected. 53 We report high infection rates with T. cruzi in adults found in sylvatic and domiciliary habitats, and lower levels of infection among the nymphal instars found in the sylvatic foci.…”
Section: Discussionmentioning
confidence: 99%
“…The paratransgenesis strategy is to introduce genes into bacteria of the mosquito midgut, instead of into the mosquito itself, and to genetically modify the bacteria, whose products also inhibit parasite development. Both of these techniques aim to replace the wild mosquitoes by disease resistant mosquitoes [8,14,22,25].…”
Section: Introductionmentioning
confidence: 99%
“…9 Moreover, semi-field trials have demonstrated the controlled spread of genetically modified symbionts in natural populations of triatominae vectors, thus reinforcing the feasibility of paratransgenesis as part of an integrated vector control program. 10,11 These achievements in insect vectors other than mosquito have strongly encouraged researchers to develop similar approaches to control MBD.…”
Section: Introductionmentioning
confidence: 99%